A systematic review and meta-analysis of poor sleep, insomnia symptoms and stress in undergraduate students. (February 2022) - Gardani, Maria; Bradford, Daniel R.R.; Russell, Kirsten; Allan, Stephanie; Beattie, Louise; Ellis, Jason G.; Akram, Umair
Summary: University students experience high prevalence of mental health problems and exacerbation of mental health difficulties, including sleep disturbances and stress during their studies. Stress and poor sleep quality and/or insomnia are interlinked outcomes for this population. The aim was to conduct a systematic review, and meta-analyses, of the relationships between sleep quality and/or insomnia with stress in students. Full-text articles of studies exploring the associations of stress with poor sleep quality and/or insomnia in undergraduate students using validated tools and published in peer-reviewed journals were eligible for inclusion. Thirty-four studies, resulting in 37 effect sizes, included and all were suitable for meta-analysis. The weighted pooled effect size between sleep quality and stress was for 0.39 (25 studies, n = 10, 065), whereas a slightly higher pooled association of 0.41 was demonstrated for insomnia and stress (12 studies, n = 5564.5). Pooled associations show moderate effects for associations between sleep quality, insomnia and stress in undergraduate students. High heterogeneity in meta-analyses was found, suggesting the findings should be considered cautiously. Future research should focus on longitudinal studies exploring sleep difficulties across the academic year, whilst university services should consider psychoeducation for stress and sleep in university students, especially during transition to university.